Kişi Adlarının Marka Olarak Tescili - (:unkn) unknown (My University, 2017)
Ad; toplumsal hayatta kişiyi başkalarından ayırt etmeye ve başkaları ile olan ilişkilerinde onu tanıtmaya yarayan sözcük veya sözcük grubudur. Kişinin adı üzerindeki hakkı, kişilik hakkının bir parçasıdır. Adın başkası tarafından haksız kullanımı kişilik hakkına saldırı teşkil eder ve bu haksız kullanım hallerinden birisi de bir kişinin adının rızası olmaksızın marka olarak tescil edilmesidir. 6769 sayılı Sınai Mülkiyet Kanunu m.6/VI hükmüne göre, adın haksız kullanımı halinde ad sahibi marka tesciline itiraz edebilir. Eğer marka tescil edilmiş ise aynı gerekçe ile hükümsüzlük davası açılması da mümkündür.

Name; is a word or group of words, that is used to differentiate a person from others in social life and to introduce him to others. The right on personal name, is a part of the right of personality. Usurpation of a name by another person commits violation of right of personality, and one of these usurpation cases is to register a person's name as a trademark without his consent. According to Article 6 / VI of the Industrial Property Law No. 6769, in case of usurpation of a name, person who has that name, can object the registration of the name as a trademark. If the trademark is registered, it is also possible to take proceedings in court for the invalidation of the trademark for the same reason.
Registration of Personal Names as a Trademark
Keywords: Hukuk